Sirkumsisi Perempuan Sebuah Tradisi Kuno yang Eksis dan Terlarang (Studi Kasus Mesir) - Pamungkas, Jati (Prodi Sosiologi Agama, 2020)
This study discusses women's circumcision. This study took a sample of women's circumcision that occurred in Egypt because women's circumcision tradition is done massively in their community. This study also discusses women's circumcision from a sociocultural perspective such as the beliefs in good things from the tradition. This study also discusses the controversies of women's circumcision tradition that the World Health Organization (WHO) considers very dangerous for women. The purpose of this study is to explain that women's circumcision tradition is an ancient tradition that existed thousands of years ago even before Islam. Women circumcision is potentially very dangerous and beliefs about good things of it that are believed by the community actually are not always realized in social facts.